Pelatihan Menciptakan Peluang Bisnis Melalui Optimalisasi Marketplace di Era New Normal Pandemi Covid 19 - Madyoningrum, Asri Winanti; Shafitranata, Shafitranata; Azizah, Rahmawati (Journal Of Human And Education (JAHE), 2024)
The new normal era after the Covid 19 pandemic was the beginning of the revival of the business world and the country's economy. The rise of the business world is really needed to move the wheels of the economy through a digital marketing approach. Community service activities aim to increase understanding of the community in efforts to optimize the marketplace, delivered by the service team of lecturers from the Al-Madani College of Economics. Implementation of service activities uses practical methods, lectures and question and answer sessions. The target training participants were 30 residents of Rajabasa Nyunyai Village, Rajabasa District, Bandar Lampung City. Implementation of community service activities is carried out offline in the Rajabasa Nyunyai Village hall. This training focuses on material on the use of digital marketing in creating business and marketing opportunities with Facebook social media facilities. This training can provide knowledge and knowledge about the world of business and business to improve the community's economy. It is hoped that this service activity can take place regularly and continuously, so that it can further increase public understanding of the use of digital technology to increase citizens' income.